A nova linguagem do Tribunal do Júri e aplicabilidade do quesito genérico de absolvição - Arcuri, Silvio José Farinholi (2018)
Law 11,689 / 2008 amended article 483, III and second paragraph of the Code of Criminal Procedure, to introduce the generic and mandatory question in all judgments of the Jury, to be voted when the materiality and authorship of the fact was recognized, so to urge the Board of Appeal to respond if "the jury acquits the accused?". Thus, a new communicative situation was inaugurated for the jury's criminal procedure, since the acquittal decision, in the previous system, would always be based on a cause provided by law, exclusion from crime or exemption from sentence, based on the evidence produced in the case. With the current system, the possibility of acquittal of the accused in the jury for supralegais causes, namely the social forgiveness (leniency), which are exclusive of punishments dissociated from the evidence of the process, was contemplated. These causes are supported by the rational discursive practices of the procedural actors and, thus, by the use of the language, in its pragmatic plane, in the plenary of the Jury. Therefore, from a "closed" system, to the civil law model, there was also a reference to an "open" model, similar to that of common law, more dialectical, in which a discursive truth is reached by which the accused should or should not be acquitted. In spite of the democratization of the verdicts of the Jury, a huge problem arose in the aspect of appealing appeals of acquittal decisions, because the absolutory, legal or supralegais theses, by the new system of questioning, have now been voted in a single question. Thus, the present work proposes a theoretical reference about the practice of rational discourse and the possible "excess of language" according to the communicative situation legally envisaged for the jury procedure, in addition to outlining the limits, motivation, control and form of appeal against absolving decisions on grounds of supralegal, a feasible solution of the applicability of the current system of questioning